PERENCANAAN STRATEGIK GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN BIOLOGI DI SEKOLAH MENENGAH ATAS - Ernita, Yenni; Mulyadi, Said; Marsithah, Iis (Hijri, 2024)
The aims of this research are (1) to find out teachers' strategic planning to improve the quality of biology learning in North Aceh Regency (2) to find out the needs assessment used by teachers to improve the quality of biology learning (3) to find out evaluations of teachers' strategic planning that can improve the quality of learning biology (4) to determine the supporting and inhibiting factors for teachers' strategic planning in improving the quality of biology learning. This research uses a qualitative approach. This research was carried out at SMAN 2 Nisam, SMAN 1 Dewantara and SMAN 1 Muara Batu, North Aceh Regency. The informants in this research consisted of teachers, students, principals and school supervisors. Data collection techniques use interviews, observation and documentation. To ensure the validity of the data using triangulation techniques with data analysis according to Miles and Hamberman. The findings of this research consist of (1) teachers prepare strategic planning at the beginning of each semester guided by the independent curriculum which is in line with the school's vision and mission, the existence of human resources and support from the community and teachers in creating a comfortable classroom atmosphere by providing teaching tools and fun methods for learning (2) Of the three schools studied, only one school has teachers who always carry out needs assessments (3) Evaluations are not often carried out only in the form of reflection on learning material, evaluations are carried out during semester exams and only teachers in one school always carry out evaluations. (4) The existence of supporting factors in the form of facilities and infrastructure, which hinder students' background and motivation, as well as the use of cellphones that are not permitted